Pengaruh Content Marketing, Harga, Dan Review Online Terhadap Keputusan Pembelian Produk Azarine Pada Shopee (Studi Kasus Mahasiswa Program Studi Manajemen Universitas Islam Malang Angkatan 2019) - Elok Faiqotul Mauludiyyah; Nurhajati Nurhajati; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract  This study was conducted to determine the effect of content marketing, price, and online reviews on purchasing decisions for azarine products at shopee (case study of students of the management study program of poor Islamic university class of 2019). This study uses explanatory research and a quantitative approach. The sample of this study was taken with purposive sampling technique with the Slovin formula used to take the sample, and the results obtained were 86 respondents. To solve the problems in this study, using validity tests, reliability tests, normality tests, multiple linear regression tests, multicollinearity tests, heteroscedasticity tests, classical assumption tests. research using multiple linear regression analysis with the help of SPSS 23. The results of this study are content marketing variables, prices, and online reviews have a significant effect on purchasing decisions, content marketing variables have a significant effect on purchasing decisions, price variables have a significant effect on purchasing decisions, and online review variables have a significant effect on purchasing decisions. Keywords: Content Marketing, Price, Online Reviews, And Purchase Decision